Brain Abnormalities in Patients with Germline Variants in H3F3: Novel Imaging Findings and Neurologic Symptoms Beyond Somatic Variants and Brain Tumors - Alves, C. A.P.F.; Sherbini, O.; D’Arco, F.; Steel, D.; Kurian, M. A.; Radio, F. C.; Ferrero, G. B.; Carli, D.; Tartaglia, M.; Balci, T. B.; Powell-Hamilton, N. N.; Schrier Vergano, S. A.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Pathogenic somatic variants affecting the genes Histone 3 Family 3A and 3B (H3F3) are extensively linked to the process of oncogenesis, in particular related to central nervous system tumors in children. Recently, H3F3 germline missense variants were described as the cause of a novel pediatric neurodevelopmental disorder. We aimed to investigate patterns of brain MR imaging of individuals carrying H3F3 germline variants. MATERIALS AND METHODS: In this retrospective study, we included individuals with proved H3F3 causative genetic variants and available brain MR imaging scans. Clinical and demographic data were retrieved from available medical records. Molecular genetic testing results were classified using the American College of Medical Genetics criteria for variant curation. Brain MR imaging abnormalities were analyzed according to their location, signal intensity, and associated clinical symptoms. Numeric variables were described according to their distribution, with median and interquartile range. RESULTS: Eighteen individuals (10 males, 56%) with H3F3 germline variants were included. Thirteen of 18 individuals (72%) presented with a small posterior fossa. Six individuals (33%) presented with reduced size and an internal rotational appearance of the heads of the caudate nuclei along with an enlarged and squared appearance of the frontal horns of the lateral ventricles. Five individuals (28%) presented with dysgenesis of the splenium of the corpus callosum. Cortical developmental abnormalities were noted in 8 individuals (44%), with dysgyria and hypoplastic temporal poles being the most frequent presentation. CONCLUSIONS: Imaging phenotypes in germline H3F3-affected individuals are related to brain features, including a small posterior fossa as well as dysgenesis of the corpus callosum, cortical developmental abnormalities, and deformity of lateral ventricles.
CRIS-Team Scopus Importer:2022-08-19